Decolonizing trauma studies: Trauma and postcolonialism - Andermahr, Sonya (MDPI AG - Multidisciplinary Digital Publishing Institute, 2016)
This Special Issue aims to explore the complex and contested relationship between Trauma Studies and postcolonial theory, focusing on the possibilities for creating a decolonized trauma theory that takes account of the suffering of minority groups and non-Western cultures, broadly defined as cultures beyond Western Europe and North America. The issue builds on the insights of, inter alia, Stef Craps's book, Postcolonial Witnessing, and responds to his challenge to interrogate and move beyond a Eurocentric trauma paradigm.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; discours dominant; décolonialisme; périodes historiques; ressource en ligne; système colonial; systèmes d'oppressions; trauma